2008
DOI: 10.1128/cvi.00408-07
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Gamma Interferon Release Assays Predict Lung Responses andMycobacterium tuberculosisDisease Outcome in Mice

Abstract: Current diagnostic tests for tuberculosis (TB) are not able to distinguish active disease from latent Mycobacterium tuberculosis infection, nor are they able to quantify the risk of a latently infected person progressing to active TB. There is interest, however, in adapting antigen-specific gamma interferon (IFN-␥) release assays (IGRAs) to predict disease outcome. In this study, we used the differential susceptibilities of inbred mouse strains to M. tuberculosis infection to evaluate the prognostic capabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 64 publications
4
56
0
Order By: Relevance
“…TB infection control in animals and humans is associated with the production of IFN-c by the CD4+ T-helper (Th)-cells [39]. It has been shown, in animal models, that a decreased production of IFN-c and a decrease in the number of IFN-c-producing cells are predictive of an increased risk of developing TB [40]. In contact patients, it has been observed that the progression to disease was associated with a decrease in IFN-c, and an increase in interleukin (IL)-10 and IL-4 levels [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…TB infection control in animals and humans is associated with the production of IFN-c by the CD4+ T-helper (Th)-cells [39]. It has been shown, in animal models, that a decreased production of IFN-c and a decrease in the number of IFN-c-producing cells are predictive of an increased risk of developing TB [40]. In contact patients, it has been observed that the progression to disease was associated with a decrease in IFN-c, and an increase in interleukin (IL)-10 and IL-4 levels [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…24,30,33 We use CBA/J mice to model pulmonary TB because these mice have no known immunological defects, are relatively susceptible to M.tb infection, and maintain long-term stable M.tb burdens. 2,3,36 Yet, the manifestation of TB disease in CBA/J mice has not been completely described. Here, we show microscopic features of TB disease in CBA/J mice and in M.tb-infected CBA/J mice that have no clinical signs.…”
Section: Cba/j Mouse Model Mycobacterium Tuberculosis Neutrophilsmentioning
confidence: 99%
“…In some experiments, mice were euthanized when 10% of their peak body weight was lost and there were no other clinical signs. The M.tb pulmonary burden was calculated by colonyforming units as previously described 3 or lungs were fixed in 10% neutral buffered formalin for hematoxylin and eosin (HE), Masson's trichrome, Von Kossa, or modified ZiehlNeelsen acid-fast staining. Slides were evaluated by a boardcertified veterinary pathologist (G. Beamer) and scanned at 40Â using an Aperio ScanScope (Aperio, Vista, CA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…people with HIV infection). Screening for the individuals most at risk of developing active TB from the huge "at-risk" reservoir of LTBI cases is an important goal of TB control efforts worldwide [6]. The prevalence of LTBI in close TB contacts is reported to be high: being a household contact is a serious risk factor associated with progression to active TB [7,8].…”
Section: Introductionmentioning
confidence: 99%